Study on the preparation technology of centrifugal Al-18Si-X composite reinforced with in situ particles. Issue 1 (1st September 2022) - Lin, Xuedong; Liu, Changming; Che, Linxian; Sun, Jian
Abstract: Al-18Si- X ( X =Mg, Ti, Ni) composite tubular castings were prepared by centrifugal casting. The microstructure of cylindrical casting of Al-18Si- X composite was observed along the radial direction, and the segregation behavior and distribution characteristics of primary particles formed in different alloys under the action of centrifugal field were studied. The results show that the in situ particles in Al-18Si-7Mg, Al-18Si-7Ti, and Al-18Si-7Ni tubular castings have different segregation behaviors under the action of centrifugal field, which results in the formation of particle reinforcing layers in different regions of the castings. It is found that the volume fraction, size and particle morphology of primary particles in particle reinforcement layer of different castings are different.